Foreign body induced vesical stone - Saroj, Jitendra Kumar; Yadav, Arpit; Rabha, Pinki; Yadav , Sonal (International Surgery Journal, 2026)
Urinary bladder stone formation due to foreign body is not well understood. But insertion of foreign body in urethra for sexual gratification is increasing and most commonly encountered in psychiatric patient. Various types of foreign body has been reported for self-insertion into urinary bladder.in this study fishing threads were used for insertion into the urinary bladder that leads to stone formation for which open cystolithotomy was performed.